Self-reported oral and general health in relation to socioeconomic position - Magnus Hakeberg; Ulla Wide Boman (BMC, 2017)
Abstract Background During the past two decades, several scientific publications from different countries have shown how oral health in the population varies with social determinants. The aim of the present study was to explore the relationship between self-reported oral and general health in relation to different measures of socioeconomic position. Methods Data were collected from a randomly selected sample of the adult population in Sweden (n = 3500, mean age 53.4 years, 53.1% women). The response rate was 49.7%. Subjects were interviewed by telephone, using a questionnaire including items on self-reported oral and general health, socioeconomic position and lifestyle. Results A significant gradient was found for both oral and general health: the lower the socioeconomic position, the poorer the health. Socioeconomic position and, above all, economic measures were strongly associated with general health (OR 3.95) and with oral health (OR 1.76) if having an income below SEK 200,000 per year. Similar results were found in multivariate analyses controlling for age, gender and lifestyle variables. Conclusions For adults, there are clear socioeconomic gradients in self-reported oral and general health, irrespective of different socioeconomic measures. Action is needed to ensure greater equity of oral and general health.